A Review of Tannin Determination Methods Using Spectrophotometric Detection in Red Wines and Their Ability to Predict Astringency - Wilhelmy, C.; Pavez, C.; Bordeu, E.; Brossard, N. (South African Journal of Enology and Viticulture, 2021)
Astringency is an important sensory attribute that influences red wine quality. The astringent sensation inside the mouth is caused by a group of molecules called tannins. These molecules can be quantified and analysed by several numbers of methods, such as the Bate Smith method, Adams Harbertson assay, and methylcellulose precipitation method. All these methods are colourimetric, however they differ on the principle on which they are based and, as well as on the tannin pool they are able to measure. In the literature, it is possible to find a wide range of concentrations of tannins for the main red wines varieties, which have been evaluated by the methods herein reviewed. For instance, higher tannin concentrations are obtained using the Bate Smith method (2.08-3.48 g/L tannin) compared with the Adams Harbertson assay (0.58-0.14 g/L tannin), which exhibit the lowest results. However, studies that directly compare results obtained with these methods are scarce. The aim of this work is to compare tannin concentrations in red wines and along with how sensory astringency correlates with tannin concentration measured by these three methods.